Kontribusi Kemampuan Berpikir Kritis, Kreatif dan Literasi Visual Dalam Pembelajaran TPS Terhadap Hasil Belajar Siswa SDN Ketabang Surabaya - Achmad Fanani; Ida Sulistyowati; Dian Kusmaharti; Indah Ayu Wulandari; Wahyu Eka Saputri (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
An educator must be able to manage learning that allows students to hone their skills in the 21st century. The abilities that can be developed in the learning process are critical thinking, creative and visual literacy skills. These abilities can be developed through learning with the Think-Pair-Share (TPS) model which is reflected in each learning stage. This study aims to determine the correlation and contribution of critical thinking, creative and visual literacy skills to learning outcomes through the application of the TPS learning model. This research is a correlational quantitative study with the research sample of fourth grade students at SDN Ketabang Surabaya, using the Random Sampling technique. Data collection techniques used critical thinking, creative, visual literacy and learning outcomes tests. The data analysis technique used is multiple linear regression. The results of data analysis can be concluded that there is a simultaneous (together) correlation between critical thinking (X1), creative (X2), and visual literacy (X3) variables on student learning outcomes (Y) significantly at r = 0.362. the contribution given by the three independent variables to the variable (Y) is 13.10%.